Implementation of Chlorella vulgaris co-culture in open pond systems for sustainable green industry development - Sitoresmi Prabaningtyas; Neena Zakia; Dhiyaudin Aridhowi; Awil Endar Pramesti; Widi Arifah; Julia Lailatul Farikah; Dita Ayu Eka Saputri (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Microalgae are promising sources of high-value biomass and renewable energy. Chlorella vulgaris is widely recognized for its ability to grow under various trophic conditions. Co-cultivation of microalgae with bacteria has the potential to enhance biomass production, although its effectiveness depends on the cultivation system. This study compared the growth performance and volatile metabolite profiles of C. vulgaris co-cultured with an Indole-3-Acetic Acid (IAA)- and vitamin B12-producing bacterial consortium in Open Pond (OP) and Photobioreactor (PBR) systems. From June to August 2025, C. vulgaris was co-cultivated with the bacterial consortium in the OP and PBR systems for 14 days. Growth was monitored by measuring cell density at 675 nm with a UV-Vis spectrophotometer, while the volatile metabolite profiles of the biomass harvested at the early stationary phase were analyzed using Gas Chromatography-Mass Spectrometry (GC–MS). The PBR system achieved a significantly higher peak cell density (9,6 x 10⁷ cells/mL) than the OP system (4,0 x 10⁷ cells/mL). GC-MS identified 136 metabolites, with the PBR system exhibiting a higher abundance of polyunsaturated fatty acids (PUFAs). Conversely, the OP system exhibited higher levels of chavicol (1.02%) and the quorum-sensing molecule farnesol (0.53%), indicating adaptive responses to environmental stress. These findings indicate that functional bacteria benefit both cultivation systems, although the OP system requires further optimization for sustainable industrial applications.